Very Short Dual Antiplatelet Therapy After Drug-Eluting Stent Implantation in Patients Who Underwent Complex Percutaneous Coronary Intervention: Insight From the STOPDAPT-2 Trial. (19th May 2021) - Yamamoto, Ko; Watanabe, Hirotoshi; Morimoto, Takeshi; Domei, Takenori; Ohya, Masanobu; Ogita, Manabu; Takagi, Kensuke; Suzuki, Hirohiko; Nikaido, Akira; Ishii, Mitsuru; Fujii, Shinya; Natsuaki, Masahiro; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Safety and efficacy of clopidogrel monotherapy after very short dual antiplatelet therapy (DAPT) is uncertain in patients undergoing complex percutaneous coronary intervention (PCI). Methods: We conducted a post hoc subgroup analysis based on the complexity of PCI in the STOPDAPT-2 trial (Short and Optimal Duration of Dual Antiplatelet Therapy-2), which randomly compared 1-month DAPT followed by clopidogrel monotherapy with 12-month DAPT after cobalt-chromium everolimus-eluting stent implantation. Complex PCI was defined as any of the following: 3 vessels treated, ≥3 stents implanted, ≥3 lesions treated, bifurcation with 2 stents, >60 mm total stent lengths, and target of chronic total occlusion. The primary end point was the composite of cardiovascular (cardiovascular death/myocardial infarction/definite stent thrombosis/stroke) and bleeding (TIMI [Thrombolysis in Myocardial Infarction] major/minor) end points. The major secondary end points were the cardiovascular and bleeding end points. Results: Among the 3009 study patients, there were 509 patients (16.9%) with complex PCI (1-month DAPT: N=245, and 12-month DAPT: N=264) and 2500 patients (83.1%) without complex PCI (1-month DAPT: N=1255, and 12-month DAPT: N=1245). There were no significant interactions between the complexity of PCI and the effects of 1-month DAPT versus 12-month DAPT on the primary end point (complex PCI: 1.67% versus 5.32%, hazard ratio, 0.30 [95% CI, 0.10–0.92], P =0.04, and noncomplex PCI: 2.50% versus 3.35%, hazard ratio, 0.75 [95% CI, 0.47–1.20], P =0.23; P interaction =0.14), and on the major secondary cardiovascular end point (complex PCI: 1.67% versus 3.04%, hazard ratio, 0.54 [95% CI, 0.16–1.79], P =0.31, and noncomplex PCI: 2.02% versus 2.39%, hazard ratio, 0.86 [95% CI, 0.50–1.47], P =0.58; P interaction =0.49). The cumulative 1-year incidence of the major secondary bleeding end point was significantly lower in the 1-month DAPT group than in the 12-month DAPT group regardless of the complexity of PCI (complex PCI: 0% versus 2.29%, log-rank P =0.02, and noncomplex PCI: 0.48% versus 1.38%, log-rank P =0.02). Conclusions: The effects of clopidogrel monotherapy after 1-month DAPT relative to 12-month DAPT for the primary and major secondary end points were comparable in complex PCI and noncomplex PCI without significant interactions. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02619760.